The synergistic effect of Fe2O3/SiO2 nanoparticles concentration on rheology, wettability, and brine-oil interfacial tension - Hassan, Y.M. (Elsevier B.V., 2022)
Various nanoparticles (NPs) have been discovered as revolutionary agents of change in reservoir properties such as rheology, interfacial tension (IFT), and surface wettability that could lead to enhanced oil displacement. In recent years, Silicon dioxide (SiO2) and various metal oxide NPs have recorded successes in oil recovery, thus, understanding composites of NPs fluids is anticipated to provide unprecedented outcomes. The present study is aimed at evaluating the synergy impact of the NPs concentrations of Fe2O3/SiO2 on rheology, IFT, and rock surface wettability. The composite of Fe2O3/SiO2 was firstly synthesized and characterized to determine its physical and chemical properties. Subsequently, nanofluids of Fe2O3/SiO2 were prepared at different concentrations using brine as a fluid dispersant phase and investigated on the rheology, IFT, and wettability at 60 Â°C. The results have shown that the dispersion stability of the Fe2O3 NPs was found to have increased from â11 mV to â38 mV when SiO2 NPs were introduced and led to an increase in the viscosity of the composite fluids from 0.88 cP to 1.95 cP. The base case IFT (brine/oil system) was observed to be 17.39 mN/m, and upon introduction of the Fe2O3/SiO2 composite, the IFT significantly reduced to 0.21 mN/m as a result of the high attachment of the NPs at the oil/fluid interface. Furthermore, combining SiO2 with the Fe2O3 has facilitated the adsorption capacity of the NPs composite leading to the spreading of the nanocomposite fluids on the surface of sandstone which eventually alters the wettability from 140.65Â° to 26.23Â°. The study has shown the synergy effect of composite NPs which resulted in reducing the IFT and wettability by 98 and 81 respectively in advance of 50â60 reductions commonly observed when individual NPs have been used. Â© 2021 Elsevier B.V.